SUR2A as a cardioprotector? - Jovanović, Aleksandar (Archives of Pharmacy, 2022)
SUR2A is a protein serving as a regulatory subunit of sarcolemmal ATP-sensitive K+ (KATP) channels. It has been shown that an increase in the myocardial level of this protein protects the heart against different types of metabolic stresses, including ischemia. An increase in SUR2A leads to an increase in the number of KATP channels, which is associated with earlier channel activation during ischemia as well as increased levels of subsarcolemmal ATP. Activation of KATP channels shortens action membrane potential to prevent Ca2+ influx while increased subsarcolemmal ATP levels provide energy for vital processes in the environment surrounding the channel. How to increase SUR2A expression in an efficient and safe manner has been considered. Two possible approaches have been found to be promising. One is a gene therapy approach with virus-containing SUR2A and the other was nicotinamide, a form of vitamin B3 rarely used in clinical practice. In experimental animals, it has been shown that oral intake of relatively small doses of nicotinamide is cardioprotective due to SUR2A increase. Not only that increased SUR2A is devoid of adverse effects, it even prolongs the lifespan in healthy animals. Based on all these findings, we believe that SUR2A-based strategies against heart ischemia deserve to be seriously considered in clinical practice. The use of nicotinamide in this context is particularly interesting, as this compound is almost devoid of adverse effects, especially in doses used to upregulate SUR2A. Such therapy would be a good adjunct to current therapies for ischemic heart disease.